Cast iron - a predictable material - Jorg C. Sturm (China Foundry, 2011)
High strength compacted graphite iron (CGI) or alloyed cast iron components are substituting previously used non-ferrous castings in automotive power train applications. The mechanical engineering industry has recognized the value in substituting forged or welded structures with stiff and light-weight cast iron castings. New products such as wind turbines have opened new markets for an entire suite of highly reliable ductile iron cast components. During the last 20 years, casting process simulation has developed from predicting hot spots and solidification to an integral assessment tool for foundries for the entire manufacturing route of castings. The support of the feeding related layout of the casting is still one of the most important duties for casting process simulation. Depending on the alloy poured, different feeding behaviors and self-feeding capabilities need to be considered to provide a defect free casting. Therefore, it is not enough to base the prediction of shrinkage defects solely on hot spots derived from temperature fields. To be able to quantitatively predict these defects, solidification simulation had to be combined with density and mass transport calculations, in order to evaluate the impact of the solidification morphology on the feeding behavior as well as to consider alloy dependent feeding ranges. For cast iron foundries, the use of casting process simulation has become an important instrument to predict the robustness and reliability of their processes, especially since the influence of alloying elements, melting practice and metallurgy need to be considered to quantify the special shrinkage and solidification behavior of cast iron. This allows the prediction of local structures, phases and ultimately the local mechanical properties of cast irons, to asses casting quality in the foundry but also to make use of this quantitative information during design of the casting. Casting quality issues related to thermally driven stresses in castings are also gaining increasing attention. State-of-the-art tools allow the prediction of residual stresses and iron casting distortion quantitatively. Cracks in castings can be assessed, as well as the reduction of casting stresses during heat treatment. As the property requirements for cast iron as a material in design strongly increase, new alloys and materials such as ADI might become more attractive, where latest software developments allow the modeling of the required heat treatment. Phases can be predicted and parametric studies can be performed to optimize the alloy dependent heat treatment conditions during austenitization, quenching and ausferritization. All this quantitative information about the material's performance is most valuable if it can be used during casting design. The transfer of local properties into the designer抯 world, to predict fatigue and durability as a function of the entire manufacturing route, will increase the trust in this old but highly innovative material and will open new opportunities for cast iron in the future. The paper will give an overview on current capabilities to quantitatively predict cast iron specific defects and casting performance and will highlight latest developments in modeling the manufacture of cast iron and ADI as well as the prediction of iron casting stresses.